Antioxidant Activity of Some Fluids Extracts of Indigenous Wild Cherry Fruits (European Journal of Natural Sciences and Medicine, 2021)
The paper presents un study regarding the comparative total antioxidant capacity of some fluids extracts of the soluble lipid compounds of Cerasus avium (L.) Moench. syn. Prunus avium (L.) var. sylvestris Ser fruits, popular named wild cherry, species undertaken aiming at exploiting the nutrient profiles and promoting the further development of these indigen phytopharmaceutical resources. For analysis, the photo-chemiluminescence method, ACL procedure, Analytik Jena AG, by comparing with the standard Trolox® solution, was used. Wild cherry fruits fluid extracts analyzed emphasize an increased total antioxidative capacity which may be attributed to the high level content of polyphenolic compounds and minerals content which sustains the possibility to use this valuable vegetal product for nutraceutical or comeceutical preparations.